Implementasi Fiqh Shalat dan Pendidikan Karakter Siswa di Sekolah Holistik Semarang - Heri Mahfudhi (STAI Terpadu Yogyakarta, 2024)
Character education is something that is very important for individual and social life, so it must always get attention to be reviewed to make it more developed and established. This study aims to explore and analyse the implementation of fiqh prayer in the context of students' character education in a holistic school in Semarang. The focus of the research involves the integration of fiqh prayer values as a foundation for shaping students' Islamic character. The research method used is qualitative research with a case study approach. Data were collected through observation, interviews, and document analysis. The results showed that the implementation of fiqh prayer in Semarang holistic school has a positive impact on students' character building. The special fiqh prayer curriculum is designed to provide an in-depth understanding of the ritual and ethical aspects of prayer, which are then integrated with Islamic character values. Interactive learning methods, religious-orientated extracurricular activities, and parental involvement are integral to this implementation effort. Students' character education through fiqh prayer in Semarang holistic school contributes significantly to the development of students' morality, self-discipline, and spiritual awareness. The findings of this study can be a reference for educational practitioners and researchers in developing a model of character education based on religious values in holistic schools and other educational institutions.